METAANALISIS PENELITIAN MOTIVASI BERPRESTASI - Japar, Muhammad; Purwati, Purwati; Sugiyadi, Sugiyadi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
The research aims to find great real correlation between achievement motivation and achievement knowing whether or not that affects veriabel moderator corelation achievement motivation with learning. Research conducted on 26 outcome studies on the relationship with learning achievement motivation. Research results show that the correlation with learning achievement motivation is actually 0.256, after correcting the correlation between 0.607 and -0.095 sd moderators are variables that affect the correlation with learning achievement motivation. Correlation for SMP = 0.460, high school = students = 0.175 and 0.258. Correlation based on location: Java = 0.239 and outside Java = 0.268.